2011
DOI: 10.1007/s10867-011-9246-4
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes in the archaerhodopsin-3 proton pump: detection of conserved strongly hydrogen bonded water networks

Abstract: Archaerhodopsin-3 (AR3) is a light-driven proton pump from Halorubrum sodomense, but little is known about its photocycle. Recent interest has focused on AR3 because of its ability to serve both as a high-performance, genetically-targetable optical silencer of neuronal activity and as a membrane voltage sensor. We examined light-activated structural changes of the protein, retinal chromophore, and internal water molecules during the photocycle of AR3. Low-temperature and rapid-scan time-resolved FTIR-differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 66 publications
(121 reference statements)
5
18
0
Order By: Relevance
“…The methods for expression, purification, and reconstitution of WT AR3 in E. coli polar lipids is similar to a previous report 24 with some modifications. Unlike typical expression of BR or archaerhodopsins in halobacterial strains 13 , which endogenously express all- trans retinal, E. coli does not express retinal and thus expression of functional archaerhodopsin requires supplementation 16 .…”
Section: Methodsmentioning
confidence: 82%
“…The methods for expression, purification, and reconstitution of WT AR3 in E. coli polar lipids is similar to a previous report 24 with some modifications. Unlike typical expression of BR or archaerhodopsins in halobacterial strains 13 , which endogenously express all- trans retinal, E. coli does not express retinal and thus expression of functional archaerhodopsin requires supplementation 16 .…”
Section: Methodsmentioning
confidence: 82%
“…(Adapted from [56].) Although, AR3 does not exhibit the same pattern of high frequency OH stretch bands seen in BR, this similarity indicates that there exists a conserved network of hydrogen bonds in both proteins which might serve as a proton wire [56].…”
Section: Structural Changes Of Internal Water Moleculesmentioning
confidence: 99%
“…In the case of BR, the detection of such broad absorbance bands has been associated with specific steps in proton transport [89,[93][94][95]. In a recent rapid-scan FTIR difference study of the light-driven proton pump from Halorubrum sodomense known as archaerhodopsins-3 broad continuum IR absorbance was discovered that is very similar to BR [56]. Fig.…”
Section: Structural Changes Of Internal Water Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…The tilting of helix F has been further defined by EPR using dipolar coupling distance measurements [1618] and by direct and dynamic visualization using high-speed AFM [19]. Elegant time-resolved molecular spectroscopic studies have identified also residue changes and water molecule movements in the E → C transition in BR [2022], but to test the generality of the conformational change in the microbial rhodopsin family, the two well-established properties of the C conformer considered here are (i) the connection of the Schiff base to the cytoplasmic side of the protein and (ii) an open channel from the Schiff base to the cytoplasm, detectable structurally as a tilting of the cytoplasmic portion of helix F away from neighboring helices.…”
Section: The Ion Pumping Mechanismmentioning
confidence: 99%